Does raising the retirement age increase employment of older workers? - Stefan Staubli; Josef Zweimüller (University of Zurich, Department of Economics, 2012)
Two pension reforms in Austria increased the early retirement age from 60 to 62 for men and from 55 to 58.25 for women. The reforms reduced early retirement by 18.9 percentage points among affected men aged 60-62 and by 22.3 percentage points among affected women aged 55-58.25. The associated increase in employment was merely 6.8 percentage points among men and 10.1 percentage points among women. The reforms had large spillover effects to the unemployment insurance program but negligible effects on disability insurance claims. Specifically, unemployment increased by roughly 10 percentage points both among men and women. Spillover effects had substantial fiscal implications. Absent spillover effects, the reduction of net government expenditures would have amounted to 264 million Euros per year. Due to higher unemployment insurance claims and associated foregone income tax revenues the actual reduction was only 148 million Euros. High-wage and healthy workers carried the bulk of the fall in net government expenditures. Low-wage and less healthy workers generated much less government savings as they either continue to retire early via disability pensions or bridge the gap to regular retirement by drawing unemployment benefits.
Keywords: J14; J26; 330; retirement age; policy reform; labor supply; disability; unemployment; Flexible Altersgrenze; Arbeitsangebot; Ältere Arbeitskräfte; Arbeitsmarktpolitik; Beschäftigungseffekt; Österreich